STRUCTURE AND CHARACTERISTICS OF PATENTED HIGH-CARBON WIRE - A. Ju. Borisenko; V. A. Lutsenko; O. V. Lutsenko; T. P. Kurenkova; V. A. Seregina; A. V. Demidov (Литьë и металлургия, 2011)
The influence of bainite structure on mechanical characteristics of wire of steel 80 after patenting is studied. The quantity and structure state of bainite, providing high complex of mechanical characteristics of high-carbon wire, is determined.